NON PERFORMING FINANCING AND EFFICIENCY OF ISLAMIC BANKS IN INDONESIA - PURWANTO PURWANTO (Journal of Business Studies and Management Review, 2021)
This research objective is to empirically investigate factors that decisively affect Non Performing Financing (NPF) of Islamic banks partially and simultaneously; the performance of Islamic banks through observing the efficiency by applying Data Envelopment Analysis (DEA) approach; and the intertemporal relationship between NPF and efficiency of Islamic banks by employing VAR model to test the hypothesis of 'Bad Management' and 'Bad Luck'. This research uses purposive sampling method and panel data where data collected from official website of each bank and Bank Indonesia. This study adopts quantitative research and has 72 observations from four banks in five quarterly years. An empirical evidence of this research indicates that partially FDR, ROA, and Exchange rate has negative significant influence towards NPF, while BI rate has the positive significant influence towards NPF. However, CAR and inflation has an insignificant effect to NPF. Simultaneously, all of the independent variables have the significant effect towards NPF which described by the value of 74.92%. The findings of DEA show the average value of Islamic banks in Indonesia is 92.85% which means Islamic Banks in Indonesia are not fully efficient. The finding also indicates that Islamic banks in Indonesia support the “Bad Luck” hypothesis, that the NPF and inefficiency of Islamic banks in Indonesia can be linked to external factors that are beyond management control rather than internal factors.